Metaphor and Analogy in Science Education
VIII, 210 p.
Keywords: This book brings together powerful ideas and new developments from internationally recognised scholars and classroom practitioners to provide theoretical and practical knowledge to inform progress in science education. This is achieved through a series of related chapters reporting research on analogy and metaphor in science education. Throughout the book, contributors not only highlight successful applications of analogies and metaphors, but also foreshadow exciting developments for research and practice. Themes include metaphor and analogy: best practice, as reasoning; for learning; applications in teacher development; in science education research; philosophical and theoretical foundations. Accordingly, the book is likely to appeal to a wide audience of science educators –classroom practitioners, student teachers, teacher educators and researchers.